Effectiveness of pilates training in improving hamstring flexibility of football players (Bangladesh Journal of Medical Science, 2015)
Objective: The kick force is effective only if the flexibility of the muscle is in accord. The stretching capacity of tendons, ligaments and capsule are very limited due to the function of articular stabilization. Pilates exercises are to be performed to improve muscular flexibility with greater movement breadth, strength and fluency. Lack of flexibility is a limiting factor for performance and being a facilitator for muscular injuries. Materials and Methods: Goniometer, Sit and reach table and Exercise mat. 30 football players were randomly distributed into two groups, Pilates group (n=15) and control group (n=15). Control group was given Ballistic, PNF and Static stretching exercises and Pilates group was given Pilates protocol respectively. Both the groups were trained 5 times a week for 4 weeks, 30 minutes each session. Pre and post outcome measures of Goniometer and sit and reach test were taken. Results: The Pilates group training reported a higher level of improvement than control group (p< 0.05).Bangladesh Journal of Medical Science Vol.14(3) 2015 p.265-269